2009
DOI: 10.1177/000348940911800201
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Education for Airway Endoscopy Skill Development

Abstract: Objectives: We evaluated lymphosonography, or contrast-enhanced, ultrasonography (US)-guided sentinel lymph node (SLN) detection, as a technique for demonstrating the lymphatic drainage of the thyroid gland. Methods: In this prospective animal study, four 50-kg Yorkshire swine underwent transcutaneous injection of a US contrast agent and methylene blue dye into the thyroid gland. Contrast-enhanced US was used to identify draining lymphatic channels and SLNs. Sentinel node biopsy was conducted. Subsequently, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 11 publications
0
44
0
Order By: Relevance
“…[26][27][28][29][30][31][32] We narratively discuss the other studies with nonrecurrent themes. [33][34][35][36][37][38][39][40][41][42][43] …”
Section: Synthesis: Comparison Of Simulation Versus Other Types Of Tesmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30][31][32] We narratively discuss the other studies with nonrecurrent themes. [33][34][35][36][37][38][39][40][41][42][43] …”
Section: Synthesis: Comparison Of Simulation Versus Other Types Of Tesmentioning
confidence: 99%
“…38 Virtual reality training: a 2-group nonrandomized study comparing high-fidelity simulation versus virtual reality for teaching airway endoscopy skills to otolaryngology residents and pediatric surgery fellows showed an association with high-fidelity simulation (N = 36, ES = 0.543) and enhanced nontime skills. 39 Type of feedback: 1 randomized study compared the type of corrective feedback given to learners during cardiopulmonary resuscitation training. The combination of instructor and automated feedback (from the defibrillator) during training versus instructor feedback only demonstrated large effects favoring combined feedback for nontime skills immediately after the intervention (N = 69, ES = 1.454).…”
Section: Figurementioning
confidence: 99%
“…A recent systematic review and meta-analysis of simulation based bronchoscopy training incorporated additional studies [42]. These studies included animal models, manikins, designed artificial models or VRS bronchoscopy and endobronchial ultrasound training [26,[43][44][45][46][47][48][49]. These studies used various differing models and demonstrated benefits from using simulation for purpose of bronchoscopy training.…”
Section: Vrs Bronchoscopy Studiesmentioning
confidence: 99%
“…The remaining studies [13, 19-23, 27, 28, 32, 34, 37, 38] either tested various training methods [20,27,28,32,34,37,38] , simulators [21][22][23]28] or a new approach to skills assessment [13,19] .…”
Section: Resultsmentioning
confidence: 99%